How Do Trust, Customer Review and Product Risk Affect Customer Engagement in Influencing Purchase Intention in e-Commerce Transactions? - Suman, Eva Faujiah; Kurniawati, Kurniawati (Universitas Proklamasi 45, 2024)
The numerous e-commerce platforms in Indonesia have driven the public to shift from conventional shopping to online transactions. The ease of use, product variety, and competitive pricing are reasons for the popularity of e-commerce. This study aims to determine the influence of Online Customer Review, Trust, and Product Risk on Purchase Intention, with Customer Engagement as a mediating variable in e-commerce transactions. The research is descriptive and quantitative, involving 221 respondents who have shopped via e-commerce platforms. The data analysis technique uses the Structural Equation Model AMOS 22 method. The results show that customer trust and reviews positively affect customer engagement and purchase intention. Additionally, customer engagement positively influences purchase intention. Lastly, product risk negatively affects purchase intention, although not significantly. The novelty of this research from the main journal is the addition of Customer Reviews as an independent variable that positively influences purchase intention and product risk as an independent variable that negatively affects purchase intention. The implication of this research suggests that online sellers should encourage customers to provide feedback on every purchase, thereby using customer reviews as an indirect promotional tool. Furthermore, product content should consider the perceived product risk by creating reliable content.